Maores (Journal of Parents and Teachers, 2014)
Maores, a fourteen-year-old girl who lived in Barcelona, is brutally murdered supposedly by a jealous pretender because Maores was going out with other boys. To avoid this kind of events, school coexistence planning in high schools shoud be improved as well as orientation work to prevent and possibly eliminate this type of events.
Keywords: opinion; adolescence; love and adolescence; family and education; violence; mediation